Stosunek państwa do kościołów w Rosji od chrztu Rusi do rewolucji październikowej : (od X w. do 1917 r.) - Byś, Jelena (Prawo Kanoniczne, 2001)
The relation ship of the state to the Church in the course of history has always been problematic. This is true especially in Eastern Europe. This article presents the most significant historical events which influenced the relations between the state and the churches in Russia from Russia’s baptism in 10th century till the October Revolution of 1917. The text reveals the gradual emergence of cesaropapism, imported from Byzance and aiming at the full subordination of the churches to the state authorities. Several historical periods can be traced to this development. The first period begins at the end of the first millennium when Russia of Kiev was baptized, and lasts till the 14th century when Russia of Moscow arose. This time is marked by the building up of the church organization and its laws which developed from the beginning in close connection with the state law. The second period embraces the church history in the Moscow Russia, i.e. under Russia tsars, from the 14th till the 17th century. The state authority and the church authority seem to have a certain tendency to be balanced. Later on, however, as the Russian state is strengthened, the tsar began to have a decisive voice as well in church and religions matters. In the third period (18th cent. - 1903) there exists a system of severe control and supervision over the churches in Russia by the absolutist monarchy. The Russian imperium devided all confessions into three categories: the orthodox one, dominant and looked upon as loyal to the state; foreign confessions, Christian including (catholic and protestant) or non-Christian were tolerated. But sects of the orthodox origin were persecuted. The law regarded these sects as dangerous and harmful and a betrayal of the orthodox faith, and prohibited public worship, the faithful were deprived of their civil rights. As late as the end of 19th century, the idea of religious tolerance and freedom was unknown in the Russian law. At the beginning of the 20th century, Russian confessional law made a great step forward when acts guaranteeing religious freedom appeared. This development during the years 1903-1917 is characteristic of the fourth period. For the first time in Russia’s history, freedom of conscience and freedom of confession were stated by the law. The intolerance which ruled in the 17th – 19th centuries was transformed into tolerance of all confessions; even of those which were earlier persecuted. Nevertheless, the Temporary Government of Russia supported the dominant position and privileges of the Russian Orthodox Church.